A reforma trabalhista e a ética do absurdo de Albert Camus - Scorpião, Raphael Varga (2020)
This dissertationseeks to analyze labor reform based on the ethics of the absurd of Albert Camus. Proceeding to a holistic analysis, it is clear that the pillar of legal and ontological support of labor law (protective principle) has been shaken. The reason of existence of labor justice collapses, from the moment that the law that was supposedly created to balance a deformed legal relationship starts to legitimize and support antagonistic attitudes to workers. It is in this context that the ethics of absurdity gains prominence and allows us to reflect on Law n. 13.467/2017 based on philosophy of existence, especially what has been called the french movement. After denoucing the absudity produced by the law itself, there is a proposal to build a new right through revolt, with the assumption of building an imaginary right guided by the poetic and erotic theories of law and the abandonment outdated concept such as the existential minimum